Love and Tolerance in the Pesrpective of Islamic Psychology - Hasanah, Muhimmatul; Ahwarumi, Biyati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the integration of local wisdom and Islamic psychology in nurturing love and tolerance at Sunan Drajat Islamic Boarding School, Lamongan, Indonesia. The research aims to analyze how Sunan Drajat’s noble values are applied in the pesantren context to shape students’ character. Using a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis. Despite extensive research on Islamic education and tolerance, few studies have explored how local wisdom traditions within pesantren function as a framework for Islamic psychology and character formation. This study fills that gap by showing how Sunan Drajat’s teachings are internalized through tazkiyatun nafs (purification of the soul), qalb salim (sound heart), and ihsan (spiritual excellence), fostering compassion and tolerance among students. The novelty of this study lies in its integration of Islamic psychological theory with indigenous pedagogical practices, positioning pesantren as a living laboratory for spiritual and social development. The findings reveal that this model strengthens psychological well-being, promotes inclusive spirituality, and contributes to global harmony through education grounded in local wisdom.